2015
DOI: 10.1038/srep13502
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility loci in lung cancer and COPD: association of IREB2 and FAM13A with pulmonary diseases

Abstract: Genome-wide association studies have identified loci at 15q25 (IREB2) and 4q22 (FAM13A), associated with lung cancer (LC) and chronic obstructive pulmonary disease (COPD). The aim of our research was to determine the association of IREB2 and FAM13A SNPs with LC and severe/very severe COPD patients. We examined IREB2 variants (rs2568494, rs2656069, rs10851906, rs13180) and FAM13A (rs1903003, rs7671167, rs2869967) among 1.141 participants (468 LC, 149 COPD, 524 smoking controls). The frequency of the minor IREB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“… 110–112 family with sequence similarity 13 member A ( FAM13A ) was identified in a GWAS as a gene that predisposes to increased susceptibility to COPD. 113 114 A subsequent study investigated the functional role of FAM13A in COPD pathogenesis and demonstrated that FAM13A induces emphysema by targeting canonical WNT signalling. 111 Increased expression of FAM13A was observed in several cell types in the lungs of patients with COPD and FAM13A-deficient mice (FAM13A −/− ) were protected against cigarette smoke-induced as well as elastase-induced emphysema development.…”
Section: Wnt Signalling In Copdmentioning
confidence: 99%
“… 110–112 family with sequence similarity 13 member A ( FAM13A ) was identified in a GWAS as a gene that predisposes to increased susceptibility to COPD. 113 114 A subsequent study investigated the functional role of FAM13A in COPD pathogenesis and demonstrated that FAM13A induces emphysema by targeting canonical WNT signalling. 111 Increased expression of FAM13A was observed in several cell types in the lungs of patients with COPD and FAM13A-deficient mice (FAM13A −/− ) were protected against cigarette smoke-induced as well as elastase-induced emphysema development.…”
Section: Wnt Signalling In Copdmentioning
confidence: 99%
“…IRP2 is associated with COPD susceptibility (5)(6)(7)(8)(9) and with pulmonary artery enlargement in COPD (70). This association may be sex specific (8,71) and independent of smoking (72,73), and it may also associate with severe alpha-1 antitrypsin (AAT) deficiency (71) and lung cancer (74,75). IRP2 is located within a cluster of genes on chromosome 15q25, which includes several components of the nicotinic acetylcholine receptor.…”
Section: Genetic and Epidemiological Evidencementioning
confidence: 99%
“…Single nucleotide polymorphisms of other genes such as FAM13A (at 4q24) that encode for a RhoGTPase-activating protein binding domain have been associated with both COPD and lung cancer [203]. Although their functional contribution to lung cancer and/or COPD remains yet to be elucidated, the involvement of Rho GTPases in the pulmonary endothelial barrier in lung suggests a potential mode of involvement for FAM13A [204]. Direct effects of nicotine have also been reported on endothelial and fibroblast cell populations.…”
Section: Genetic Predispositionmentioning
confidence: 99%